Immersive 3D Holoscopic Video System - Aggoun, A. (2013)
We demonstrated a 3D holoscopic video system for 3DTV application. We showed that using a field lens and a square aperture significantly reduces the vignetting problem associated with a relay system and achieves over 95 percent fill factor. The main problem for such a relay system is the nonlinear distortion during the 3D image capturing, which can seriously affect the reconstruction process for a 3D display. The nonlinear distortion mainly includes lens radial distortion (intrinsic) and microlens array perspective distortion (extrinsic). This is the task of future work. Our results also show that the SS coding approach performs better than the standard HEVC scheme. Furthermore, we show that search and retrieval performance relies on the depth map's quality and that the multimodal fusion boosts the retrieval performance.